Capturing institutional change: the case of the right to information act in India - Jha, Himanshu (Institutions and development in South Asia series, 2020)
This is the first book in the 'Institutions and Development in South Asia' series. It studies the historical institutionalism in the information regime in India by presenting an alternative narrative about the evolution of the RTI Act.